Pembinaan Al-Qur’an Serta Penanaman Moral kepada Siswa Musala Al-Muhakim Randutata Paiton Probolinggo - Abd. Basid; Rifqatul Husna; Abd. Somad; Luthviyah Romziana (PARTISIPATORY, 2025)
The community service activities (PkM) that we conducted were aimed at making students of Musala Al-Muhakim Randutata Paiton Probolinggo accustomed to reading the Qur'an fluently and fluently, and forming good morals. We chose the halaqah learning method because in our opinion this method is the most effective. The first solution is to hold teaching and learning activities (KBM) to read the Qur'an and also deepen the knowledge of reading the Qur'an, such as Tajwid Science and makharij al-khuruf based on the halaqah that has been determined previously. And the second solution includes knowledge (cognitive), feelings (feeling), and actions (action). After carrying out community service (PkM) at Musala Al-Muhakim Randutata Paiton Probolinggo, we can conclude that community service activities (PkM) have a positive effect on students of Musala Al-Muhakim Randutata Paiton Probolinggo in fluency in reading the Qur’an and improving morals.